STUDENTS' PERCEPTION TO THE USE OF "MALEFICENT" MOVIE AS INSTRUCTIONAL MEDIA IN LEARNING ENGLISH AT SMPN 02 GALESONG SELATAN (Karya Ilmiah Mahasiswa (KIMA), 2026)
The purpose of this study is to characterize students’ perception to the use of “Maleficent” movie as instructional media in learning English at SMPN 02 Galesong Selatan. Movie are among the many different kinds of media that are utilized in EFL lessons as instructional media for English language acquisition. Nine junior high school students in their second year participated in this study. In order to collect data, interviews were created. Following multiple movie-based teaching sessions in their EFL classrooms, the participants were questioned about their opinions regarding the usage of movie. The findings demonstrate that students at this institution are open to and receptive to using movies as material in their EFL lectures. The findings also show that students think watching movie as a instructional media for English is beneficial and engaging for them. The purpose of this research is to determine whether or not using movie as a media in English as a foreign language classes is beneficial. The findings of this research will be helpful to teachers of English as a foreign language as well as students studying the language because they will enable other teachers to decide whether or not to use movie as a media in their own teaching settings.